Transvaginal PVDF-mesh for cystocele repair: A cohort study. (March 2017) - Barski, Dimitri; Arndt, Christian; Gerullis, Holger; Yang, Jin; Boros, Mihaly; Otto, Thomas; Kolberg, Hans-Christian
Abstract: Introduction: Optimized biocompatibility of new materials is a major requirement for transvaginal meshes for pelvic organ prolapse (POP) repair. Polyvinylidene fluoride (PVDF) presented good characteristics in prior animal experiments and clinical use in humans. Methods: Between 01/2012 and 04/2016 37 women underwent transvaginal repair of symptomatic prolapse of the anterior vaginal wall (cystocele) with PVDF-mesh in a single institution. A chart review for recurrence, continence, peri- and early postoperative complications was performed. Referring practitioners were interviewed by telephone and mail. Additionally patient reported outcome and satisfaction were measured by Patient Global Improvement Inventory (PGI-I) scale. Results: 34 women were eligible for a mean follow up of 19 months. The functional outcome improved significantly. One symptomatic vault prolapse (2.9%) and two reoperations for incontinence (5.9%) occurred. Two mesh exposures (5.9%) occurred and were treated conservatively. No other severe complications were registered. 87.5% of treated women felt very much better or much better and would undergo the surgery again. A cohort study including development steps in accordance with the IDEAL system is presented. Conclusions: For the first time we report on effectivity and safety of transvaginal application of PVDF-mesh in real-life practice. A prospective long-term evaluation in a registry is justified. Highlights: PVDF- mesh is feasible for transvaginal application for cystocele repair. 15% of patients presented any kind of complications and 8.8% needed a resurgery for SUI or POP during the follow-up. Improvement of quality of life was reported by 87.5% according the PGI-I. The preliminary results support the initiation of prospective trial and registry according to IDEAL.